2011
DOI: 10.1038/nmat3172
|View full text |Cite
|
Sign up to set email alerts
|

Induction of coherent magnetization switching in a few atomic layers of FeCo using voltage pulses

Abstract: The magnetization direction of a metallic magnet has generally been controlled by a magnetic field or by spin-current injection into nanosized magnetic cells. Both these methods use an electric current to control the magnetization direction; therefore, they are energy consuming. Magnetization control using an electric field is considered desirable because of its expected ultra-low power consumption and coherent behaviour. Previous experimental approaches towards achieving voltage control of magnetization switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
637
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 702 publications
(661 citation statements)
references
References 24 publications
15
637
6
Order By: Relevance
“…A Japanese group found large changes in the anisotropy of magnetic thin films in TMR junctions under application of high electric fields [12]. A bistable toggle switching of the magnetization direction between two bistable orientations has been reported very recently by the same group [13]. Against this background, we used a scanning tunneling microscope (STM) to study MEC and were able to demonstrate for the first time bistable switching of the magnetic order on the nanoscale.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…A Japanese group found large changes in the anisotropy of magnetic thin films in TMR junctions under application of high electric fields [12]. A bistable toggle switching of the magnetization direction between two bistable orientations has been reported very recently by the same group [13]. Against this background, we used a scanning tunneling microscope (STM) to study MEC and were able to demonstrate for the first time bistable switching of the magnetic order on the nanoscale.…”
Section: Introductionmentioning
confidence: 84%
“…The presence of a constant electric field may influence the magnetic order, but it does not break time reversal symmetry and thus cannot be used to switch between two bistable magnetization directions of a ferromagnet. Two years later, in the same group, Shiota et al [13] showed that in a TMR junction the magnetization can be switched between two orientations by nanosecond voltage pulses. Using asymmetrically shaped voltage pulses, they could break time reversal symmetry and induce a coherent rotation of the magnetization.…”
Section: Magnetoelectric Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the voltage-induced magnetization switching was demonstrated for FeCo thin films [1]. The idea to control magnetization by the electric field has been proposed as a multiferroic concept, and has been realized, for instance, in BiFeO 3 , which is one of the most typical multiferroic materials.…”
Section: Introductionmentioning
confidence: 99%
“…13 Theoretically, the electric field effect on the MCA was investigated for various free-standing magnetic metal films 10,14-17 and Fe/MgO interfaces. 18,19 Very recently, electrically induced bistable magnetization switching was realized in MgO-based magnetic tunnel junctions at room temperature, 20,21 demonstrating the capabilities of this approach for magnetic data storage applications. 22 Alternatively, the interface magnetic anisotropy (and hence the magnetization orientation) may be tailored electronically by the ferroelectric polarization of an adjacent ferroelectric film.…”
mentioning
confidence: 97%